The Mineralogical Composition of Samos Zeoliitic Rocks and their potential use as Feed Additives and Nutrition Supplements - Filippidis, Anestis; Mytiglaki, Christina; Kantiranis, Nikolaos; Tsirambides, Ananias (Bulletin of the Geological Society of Greece, 2020)
Fifteen (15) zeolitic rocks from Karlovassi-Marathokampos basin of Samos Island (Greece) were investigated for their mineralogical composition by X-Ray Diffraction (XRD) method. According to EU Regulation No 651/2013, clinoptilolite of sedimentary origin with ≥80 wt% clinoptilolite, ≤20 wt% clay minerals, free of fibres and quartz, can be used as feed additive for all animal species. Depending on the zeolites, the zeolitic rocks are grouped to those containing: Clinoptilolite (33-86 wt%), clinoptilolite (59 wt%) + mordenite (20-21 wt%), clinoptilolite (22 wt%) + analcime (29 wt%), clinoptilolite (17 wt%) + phillipsite (27 wt%), analcime (29-70 wt%), mordenite (62%) and chabazite (63 wt%). None of the clinoptilolite-containing rocks (10 samples) meet the requirements of the EU Regulation No 651/2013, and thus cannot be used as feed additives for all animal species and consequently as nutrition supplements, since all of them contain 2-5 wt% quartz, two of them 20-21 wt% mordenite (fibrous zeolite), nine of them <80 wt% clinoptilolite (17-73 wt%) and two of them >20 wt% clay minerals (27-42 wt%). Although the EU Regulation No 651/2013 refers to clinoptilolite of sedimentary origin, using the presence or absence of quartz and fibrous minerals, none of the five mordenite, analcime and chabazite containing zeolitic rocks, can be used as feed additives and nutrition supplements, since all of them contain 2-6 wt% quartz and one of them contains 62 wt% mordenite (fibrous zeolite).